2014
DOI: 10.1016/j.bbr.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on the neural correlate of moral decision making processes

Abstract: Highlights: We compared the neural substrate of moral functioning between Koreans and Americans.  Koreans showed increased activity in the putamen, DLPFC, and postcentral sulcus.  Americans showed increased activity in the ACC and FPC.  Results support the idea of interactions between culture, education, and brain. These findings support the ideas of the interactions between the cultural background, education, and brain development, proposed in the field of cultural psychology and educational psychology.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 58 publications
(120 reference statements)
3
47
0
2
Order By: Relevance
“…The comparison showed that the MPFC was particularly activated under the moral-personal condition, while the parietal lobule regions were significantly activated under the moral-impersonal condition. These wholebrain t-tests successfully replicated previous fMRI investigations that utilized similar moral dilemmas [25,26,51]. Second, we conducted PPI analyses by setting two seed regions in the CMS, i.e., the MPFC and PCC.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The comparison showed that the MPFC was particularly activated under the moral-personal condition, while the parietal lobule regions were significantly activated under the moral-impersonal condition. These wholebrain t-tests successfully replicated previous fMRI investigations that utilized similar moral dilemmas [25,26,51]. Second, we conducted PPI analyses by setting two seed regions in the CMS, i.e., the MPFC and PCC.…”
Section: Discussionsupporting
confidence: 67%
“…The present study utilized a set of moral dilemma questions initially developed by [25,26] and used by [51]. A total of sixty dilemma questions were included in the set.…”
Section: Dilemma Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous functional neuroimaging studies have consistently demonstrated that the ventromedial prefrontal cortex (VMPFC) and orbitofrontal cortex (OFC), which constitute the DMN, were significantly associated with prosocial and moral emotion and moral cognition Reniers et al 2012;Han et al 2014Han et al , 2016Sevinc and Spreng 2014). Given these findings, the DMN is the core of moral self, and the region of interest in virtue ethics and character psychology.…”
Section: Neuroimaging Methods To Measure Moral Virtuementioning
confidence: 91%